Strategic Options for Agriculture and Development in Malawi - Dorward, Andrew R.; Chirwa, Ephraim (International Food Policy Research Institute, 2015)
This paper considers potential strategic options for agriculture and development in Malawi in the context of the country’s current situation and the prospects the country faces. After briefly reviewing current national and sectoral policy and potential roles of smallholder agriculture in economic growth, we set out the current situation in order to consider strengths, weaknesses, opportunities and threats. We conclude that a major emphasis is needed on supporting changes that reduce the rate of population growth and promote capacity for adaptation and resilience to climate change. Rapid increases in the productivity of agricultural land and labor and in rural incomes will be critical to this, alongside increased education and empowerment of girls and women. There are, however, difficult potential trade-offs to negotiate (for example, between increased irrigation and reduced inflows into Lake Malawi) and these need further consideration.